Acute Renal Failure after Abdominal Trauma: Renal Artery Spasm Hypothesis in Ischemic Infarction in a 12-Year-Old Girl. (15th September 2020) - Roussel, Aphaia; Delbet, Jean-Daniel; Ulinski, Tim
Abstract : Posttraumatic renal failure is often due to postischemic renal infarction, caused by identified vascular lesions. In our patient, a 12-year-old girl with acute anuric renal failure requiring hemodialysis after severe abdominal trauma, no vascular lesion or thrombosis was identified. Nevertheless, CT-scan and renal biopsy showed typical lesions of diffuse bilateral renal ischemic necrosis. The main hypothesis is a severe bilateral arterial vasospasm after a blunt abdominal trauma. The patient recovered only partially with persisting chronic renal failure.